Cell-penetrating peptides as drug delivery system for SiRNA. - Meriska Sudarmadji. (2012)
In recent years, siRNA has gained a lot of attention in biomedical research field due to its ability to modulate specific protein expressions – a crucial factor in treating inflammation-related diseases. In the cytoplasm, siRNA assembles into RNA-induced silencing complex (RISC), facilitating the removal of target mRNA molecules that bind to RISC antisense strand. Therefore, siRNA is very potent in silencing any genes of interest. Nevertheless, siRNA’s potency is hampered by its inability to penetrate cell membrane. Thus, finding a suitable delivery vehicle to the cell is pivotal for siRNA to exert its effect.